The role of oxytocin in modulating interpersonal space: A pharmacological fMRI study. (February 2017) - Cohen, Daniela; Perry, Anat; Gilam, Gadi; Mayseless, Naama; Gonen, Tal; Hendler, Talma; Shamay-Tsoory, Simone G.
Highlights: We show that intranasal oxytocin (OT) increases personal distance from strangers. OT reverses the activity of the left dorsomedial prefrontal cortex (dmPFC). Under OT we observed higher activation in the dmPFC when a friend is approaching. The effect of OT on personal space depends on the protagonist. Abstract: Interpersonal space is a nonverbal indicator of affiliation and closeness. In this study we investigated the effects of oxytocin (OT), a neuropeptide known for its social role in humans, on interpersonal space. In a double blind placebo controlled study we measured the effect of intranasal OT on the personal distance preferences of different familiar (friend) and unfamiliar (stranger) protagonists. Behavioral results showed that participants preferred to be closer to a friend than to a stranger. Intranasal OT was associated with an overall distancing effect, but this effect was significant for the stranger and not for the friend. The imaging results showed interactions between treatment (OT, placebo) and protagonist (friend, stranger) in regions that mediate social behavior including the dorsomedial prefrontal cortex (dmPFC), a region associated with the mentalizing system. Specifically, OT increased activity in the dmPFC when a friend approached the participants but not when a stranger approached. The results indicate that the effect of OT on interpersonal space greatly depends on the participant's relationship with the protagonist. This supports the social salience theory, according to which OT increases the salience of social cues depending on the context.